1, 7‐Bay‐Substituted Perylenediimide Derivative with Outstanding Laser Performance. Issue 12 (11th November 2013) - Ramírez, Manuel G.; Pla, Sara; Boj, Pedro G.; Villalvilla, José M.; Quintana, José A.; Díaz‐García, María A.; Fernández‐Lázaro, Fernando; Sastre‐Santos, Ángela
<x xml:space="preserve">Abstract</x> Efficient ASE at wavelengths >620 nm from PS films doped with a bay‐substituted perylenediimide (PDI) derivative is reported. The maximum PDI content is around 40 times larger than in prior studies. The ability to introduce large dye amounts into the film without photoluminescence (PL) quenching allows very high PL and ASE efficiencies with low thresholds. A distributed feedback (DFB) laser device using one of the best‐performing films is fabricated and characterized. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>